The Effectiveness of Laser Applications and Photodynamic Therapy on Relevant Periodontal Pathogens (Aggregatibacter actinomycetemcomitans) Associated with Immunomodulating Anti-rheumatic Drugs - Maria-Alexandra Martu; Ionut Luchian; Mihai Mares; Sorina Solomon; Oana Ciurcanu; Vlad Danila; Elena Rezus; Liliana Foia (Bioengineering, 2023)
Considering the current context of the increasing resistance of bacterial species to antibiotics and other antimicrobial agents, a major objective is to develop other antimicrobial approaches, which would be able to inactivate pathogens with considerable effectiveness. Two such methods are photodynamic disinfection therapy and laser irradiation. In view of the immunocompromised status of some patients under immunosuppressive therapy and potential drug interactions that can be established between systemic antimicrobial agents, the research of local, minimally invasive methods of inactivating periodontal pathogens in the context of these systemic therapies with modifying drugs of the immune response is justified. This in vitro study evaluated the antimicrobial action of a diode laser, wavelength 940 nm, and photodisinfection therapy at 670 nm (photosensitizer, 3,7 dimethyl phenothiazine chloride) on a type strain of Aggregatibacter actinomycetemcomitans, a known periodontal pathogen, in the presence and absence of active substances used in autoimmune disease therapy (Etanercept, Infliximab, Metothrexate). The association of a conventional antirheumatic drug with anti-TNF-α therapy determined a significantly greater inhibition of the strain of A. actinomycetemcomitans compared to monotherapy, in vitro. Photodisinfection caused a significant reduction in bacterial burden after a 30 s exposure in vitro, regardless of the pharmaceutical associations of biological and conventional disease-modifying antirheumatic drugs (DMARDs). Irradiation with a diode laser for 30 s at a power of 5 W caused a greater reduction compared to irradiation with 1 W. The application of laser and photodisinfection induced a significant reduction in Aggregatibacter actinomycetemcomitans in vitro and could be considered important adjunctive measures for the eradication of this oral pathogen in the context of immunomodulating therapy.